2008
DOI: 10.1098/rsif.2007.1308
|View full text |Cite
|
Sign up to set email alerts
|

Sliding-induced adhesion of stiff polymer microfibre arrays. I. Macroscale behaviour

Abstract: Gecko-inspired microfibre arrays with 42 million polypropylene fibres cm K2 (each fibre with elastic modulus 1 GPa, length 20 mm and diameter 0.6 mm) were fabricated and tested under pure shear loading conditions, after removing a preload of less than 0.1 N cm K2 . After sliding to engage fibres, 2 cm 2 patches developed up to 4 N of shear force with an estimated contact region of 0.44 cm 2 . The control unfibrillated surface had no measurable shear force. For comparison, a natural setal patch tested under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 34 publications
10
138
1
3
Order By: Relevance
“…While Lee et al (2008) showed low peel strength (0.15 N m K1 ) on the whole patch, here a frictional adhesion effect was observed during normal pull-off with a spherical probe, whereby the normal tensile force was proportional to shear force. Repeated LDP testing showed that fibre arrays continue to function after more than 100 experiments, and they gain shear force and pull-off force with each trial.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…While Lee et al (2008) showed low peel strength (0.15 N m K1 ) on the whole patch, here a frictional adhesion effect was observed during normal pull-off with a spherical probe, whereby the normal tensile force was proportional to shear force. Repeated LDP testing showed that fibre arrays continue to function after more than 100 experiments, and they gain shear force and pull-off force with each trial.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly to Lee et al (2008), LDP tests demonstrated increasing shear forces during sliding. While Lee et al (2008) showed low peel strength (0.15 N m K1 ) on the whole patch, here a frictional adhesion effect was observed during normal pull-off with a spherical probe, whereby the normal tensile force was proportional to shear force.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations